Eye damage in a patient with syphilis/HIV coinfection. A clinical case - O. K. Loseva; R. G. Tuaeva; O. V. Zhukova; T. P. Bessarab; E. A. Kleshcheva; G. Sh. Safina (Российский офтальмологический журнал)
In recent years, the literature has been discussing the issues of diagnosis and managing damaged eye patients who suffer from syphilis/HIV coinfection. We present a clinical case of syphilitic uveitis in the patient’s third reinfection of syphilis, which occurred during a long-term HIV infection. The causes for insufficient treatment effectiveness are analyzed.